ANALISIS BAHASA AGAMA DALAM KEHIDUPAN BERAGAMA MENURUT ALIRAN POSITIVISME LOGIS - Eka Safitri; Ihsan Sa'dudin (JURNAL YAQZHAN: Analisis Filsafat, Agama dan Kemanusiaan, 2022)
This paper seeks to reveal and analyze the language of religion in the perspective of logical positivism. Where the discussion of religious languages is a complicated and much debated discussion. In the philosophy of flow which criticizes the language of religion is a logical flow of positivism because according to the flow of logical positivism everything that cannot be measured has no meaning. This flow is more concerned with efforts to determine the meaning or meaninglessness of a statement in philosophy and science, not on the statement whether right or wrong. In the language of religion, first, the expressions used to explain the object of metaphysical thought, especially about God. Second, the language of the scriptures, especially the language of the Qur'an. Third, the language of religious ritual is so real, the strength and function of a religious symbol. It can be concluded that the flow of logical positivism philosophy with religion cannot be connected because it has a different language scope, which repels each other regarding the discussion of logical positivism having the principle of verification in the language of religion about divinity (metaphysics).